A comparison between land and sand-based tests for beach volleyball assessment - Bishop, D. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: Vertical-jumping ability is critical for success in beach volleyball. However, as beach volleyball is a relatively new sport, its testing procedures have largely been adopted from the indoor game and are consequently performed on firm surfaces. The purpose of this paper was to determine whether vertical-jumping ability is specific to the test surface (i.e., wood or sand). Methods: Eighteen beach volleyball players performed 4 different vertical jumps on a wood surface or on the sand, followed by the alternate surface, in a random, counterbalanced order. Correlation coefficients were calculated to determine the degree of association between the 4 jumps and between the test results on the 2 surfaces. Results: When compared with the land condition, all jump heights were significantly lower when performed on sand (p<0.05). There was however, a significant correlation between the land and sand results for all jumps (mean r=0.93; p<0.05). While all 4 vertical jump variations were significantly correlated with each other (mean r=0.91; p<0.05), the correlation between static jumps and the spike jump (3-step run up) tended to be lower. Conclusion: It is likely that vertical jump height on sand is lower than on land due to a reduction in the ground reaction force. However, despite this, the strong correlation between land and sand scores suggests that vertical-jumping ability exists as a general quality and is not greatly influenced by test surface in the subjects tested. This suggests that land-based tests can be used to assess sand jumping ability in experienced beach volleyball players.